Association between Breastfeeding and Complementary Feeding Practices and Infant Growth in the Builsa District - Abang, C. (University of Ghana, 2013)
Background: Exclusive breastfeeding (EBF) for six months confers several benefits to infants. It reduces infections and mortality and improves mental and motor development. The prevalence of EBF in Ghana is far from optimal having reduced from 63% in 2008 to 46% in 2011. Poor feeding practices during early childhood have been shown to contribute to stunting. The Upper East region of Ghana has 32% of its children under five stunted. Objective: To assess breastfeeding and complementary feeding practices and the association between duration of EBF with the growth of infants at six months of age in the Builsa district in the Upper East region. Methodology: The study was conducted in two parts. The first was a qualitative study utilizing focus group discussions (FGDs) with mothers with six months old infants recruited from six communities in the Builsa district. The second was a cross-sectional survey of 290 mother-child pairs recruited from six health facilities in the Builsa district. Semi-structured questionnaires were used to collect data on socio-demographic characteristics, infant and young child feeding practices, factors affecting feeding practices and child morbidity. Data on infant nutritional status were obtained through anthropometric measurements. Duration of EBF was collected through mothers’ recall. Infants were grouped based on the duration of EBF; short (≤ 4 months) and long (5-6 months). Bivariate analyses were done to determine the relationship between the duration of EBF and infant growth, breastfeeding and complementary feeding practices and socio-demographic factors. Binary logistic regression was used to identify the predictors of long duration of EBF. Results: Results showed that cultural beliefs underline most of the breastfeeding and complementary feeding practices. Early and late introduction of complementary food, water and traditional herbs/liquids to newborn babies are common. Grandmother’s support for EBF, thickness of porridges and age of introduction of complementary food were significantly associated with duration of EBF (p=0.007; p=0.004 and p<0.001, respectively). Prevalence of underweight, stunting and wasting in the total sample was 26%, 27% and 37% respectively. Mean weight was significantly higher for infants in the long duration than infants in the short duration of EBF (7.49 ± 1.00 Kg and 7.17 ± 0.90 Kg respectively) p=0.004. Mean WLZ was also significantly better for infants in the long duration than those in the short duration of EBF (-0.50 ± 1.11 and -0.86 ± 0.98 respectively) p=0.004. Mean LAZ was significantly better for infants in the short duration than those in the long duration of EBF (0.20 ± 1.04 and -0.13 ± 1.05 respectively) p=0.007. Duration of EBF was not associated with infant growth at 6 months of age. Predictors of long EBF were grandmother’s support for EBF (OR: 2.03; 95% CI, 1.16, 3.57), having at least primary/JHS/middle school education (OR: 2.32; 95% CI, 1.25, 4.31) and being a salaried worker (OR: 4.72; 95% CI, 1.10, 20.29). Mothers who earned monthly incomes above GH¢100.00 were less likely to exclusively breastfeed for long duration compared to mothers who did not earn any monthly income (OR: 0.22; 95% CI, 0.06, 0.79). Conclusion: There is the need to promote optimal feeding practices among mothers and other persons involved in child feeding and education programs to increase knowledge in nutrition so as to enhance good nutritional status of children.
Thesis (MPHIL)-University of Ghana, 2013